Agressão no futebol - Brito, Josete Maria Cachenski (1986)
The subject under consideration -'Aggression in' soccer games' -has as a primary goal to draw a broad overview of the problems that are brought about by aggression in this popular sport in Brazil. The work is structured in such a manner to be altogether of an introductory, exploratory and descriptive nature on all main aspects relating to the major problem. The overall analysis is thus closely linked to, the various opinions and positions that have already been expressed by a number of previous authors who have dwelled on the same theme. However, it carries a well-weighted intention of being innovative. In order to show our subject under the best light possible, we have narrowed its focus to a very specific point - the in-field soccer game. For the banefit of all participants in the present meeting, we carefully guide our main spotlight towards the leading role played by managers, coaches, sports physicians, field judges, physical trainers, sports lawyers and psychologists. In short, we drive our attention to people directly involved with the phenomenology of sports in general in our contemporary society, as well as with the means to fight the problems posed by aggression, a feature that is particularly relevant to soccer players under situations of strong competition. In the second part of our work, we had the opportunity of making some personnal and direct contacts with many well-known soccer players in Brazil, as well as with other kind of professionals who deal with the sport. It should be pointed out that such an array of contacts developped a series of close observations not only while training were being played but also in the course of a number of through games final cup games. Together with some live interviews they do provide, when all pieces fall in place, a most complete picture of mutually interactive factors in soccer games. Generally speaking, the best fit model for the proposed work was felt to have to be based upon a direct observation of the research field, undertaken with a view to togathering enough data, for one of its main objectives was to sample meaningful situations. With such material in our hands we could then reformulate some vital questions that could well enrich today's psychology knowledge in this field. Undoubtedly the present emphasis on the question of aggression is an ever-growing preoccupation. The means to fight aggression are not easy to incase in one simply worded solution, but the research we have made seems to point to the conclusion that aggression is a phenomenon to be tackled already in the very early stages of all 'soccer schools'.